Kainic acid and nitrergic neurons in immature hippocampus - Jandová, K; Riljak, V; Pokorný, J; Langmeier, M (Prague medical report, 2006)
Using histochemical analysis the effect of intraperitoneal administration of kainic acid on hippocampal neurons was studied. 18-day-old male rats of the Wistar strain received kainic acid (10mg/kg) in one dose. Two days later, the 20-day-old animals were transcardially perfused with 4% paraformaldehyde under deep thiopental anaesthesia. Cryostat sections were stained to identify NADPH-diaphorase positive neurons that were then quantified in the CA1 and CA3 areas of the hippocampus, in the dorsal and ventral blades of the dentate gyrus and in the hilus of the dentate gyrus. Combination of the Fluoro-Jade B and bis-benzimide (Hoechst 33342) was used in the same areas, to identify possible neurodegeneration. After the kainic acid administration the number of NADPH-d positive neurons was lower in CA1 and CA3 areas of the hippocampus and in the hilus of the dentate gyrus, compared to the control group which we consider as baseline. Fluoro-Jade B staining detected a moderate density of neurodegeneration after KA administration in CA3 and CA1 areas of the hippocampus and the hilus of the dentate gyrus.
Keywords: krysa rodu Rattus; mužské pohlaví; Male; kyselina kainová; Nitrergic Neurons; nitrergní neurony; degenerace nervu; Rats; NADPH Dehydrogenase; hipokampus; Excitatory Amino Acid Agonists; potkani Wistar; Nerve Degeneration; Animals; zvířata; Kainic Acid; Rats, Wistar; agonisté excitačních aminokyselin; Hippocampus; NADPH-dehydrogenasa